Digital Literacy and Cashless Payment: Evidence from Indonesia - Pudin, Ahmad Syarif; Karyani, Etikah; Pamungkas, Putra; Achsanta, Aldy Fariz (The Asian Journal of Technology Management (AJTM), 2024)
Abstract. Digital financial literacy is an important factor in a person's economic behavior. A person who has a high level of digital literacy will use financial services to obtain the maximum benefit from the financial services used. In payment behavior, a person with a high level of literacy will use the payment system that provides the most financial benefits. However, there are various literatures that provide varying results regarding the impact of digital financial literacy on payment system usage. Therefore, in this study, we empirically examine the impact of digital financial literacy on the use of payment systems, especially cashless at the provincial level in Indonesia. We use 136 observations per province year for the period 2019 - 2022 to test our empirical model covering 34 provinces. We find that overall, digital financial literacy has no effect on the use of non-cash payment systems.  Keywords: Financial literacy, digital, cashless, payment, financial literacy